2019
DOI: 10.1093/mnrasl/slz128
|View full text |Cite
|
Sign up to set email alerts
|

Universe opacity and Type Ia supernova dimming

Abstract: In this paper, I revoke a debate about an origin of Type Ia supernova (SN Ia) dimming. I argue that except for a commonly accepted accelerating expansion of the Universe, a conceivable alternative for explaining this observation is universe opacity caused by light extinction by intergalactic dust, even though it is commonly assumed that this effect is negligible. Using data of the Union2.1 SN Ia compilation, I find that the standard ΛCDM model and the opaque universe model fit the SN Ia measurements at redshif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…The opaque universe model is the flat Einstein-de Sitter model (EdS) with a non-zero opacity, being described by the Hubble constant H 0 = 67.2 km s −1 Mpc −1 , dark energy Ω Λ = 0 and the B-band opacity λ B = 0.09 mag Gpc −1 . The model parameters were obtained by fitting the SN Ia Pantheon data using the method of Vavryčuk (2019). The residua between both theoretical models and the measurements follow the normal distribution ( Fig.…”
Section: Type Ia Supernovae Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The opaque universe model is the flat Einstein-de Sitter model (EdS) with a non-zero opacity, being described by the Hubble constant H 0 = 67.2 km s −1 Mpc −1 , dark energy Ω Λ = 0 and the B-band opacity λ B = 0.09 mag Gpc −1 . The model parameters were obtained by fitting the SN Ia Pantheon data using the method of Vavryčuk (2019). The residua between both theoretical models and the measurements follow the normal distribution ( Fig.…”
Section: Type Ia Supernovae Observationsmentioning
confidence: 99%
“…The Bband opacity of the fiducial model is λ B = 0.09 mag Gpc −1 and fits the SN Ia Pantheon dataset. The fitting procedure is described in Vavryčuk (2019), where the SN Ia Union2.1 dataset was analyzed.…”
Section: Low-redshift Data (Z < 15)mentioning
confidence: 99%
“…( 22) means that the radiation pressure due to absorption acts against the gravity. The dark energy is missing in Eqs (18-20), because the Type Ia supernova dimming can successfully be explained by cosmic opacity, as discussed in Vavryčuk (2019).…”
Section: Friedmann Equations For the Opaque Universementioning
confidence: 99%
“…Neglecting cosmic opacity produced by intergalactic dust may lead to distorting the observed evolution of the luminosity density and the global stellar mass density with redshift (Vavryčuk 2017b). Non-zero cosmic opacity may invalidate the interpretation of the Type Ia supernova (SNe Ia) dimming as a result of dark energy and the accelerating expansion of the Universe (Aguirre 1999a,b;Aguirre & Haiman 2000;Ménard et al 2010a;Vavryčuk 2019). Intergalactic dust can partly or fully produce the cosmic microwave background (CMB) (Wright 1982;Bond et al 1991;Narlikar et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The cosmic acceleration rate and the cosmological parameters determined by the SNe Ia measurements are highly dependent on the possible dimming effect as well. Vavrycuk et al (2019) [36] revived a debate about an origin of Type Ia supernova (SN Ia) dimming and showed that the standard ΛCDM model and the opaque universe model (caused by light extinction by intergalactic dust) fit the SN Ia measurements at redshifts z < 1.4 fairly well. Then, there are still some possible loopholes in the current SNe Ia observations and alternative mechanisms contributing to the acceleration evidence or even mimicking the dark energy behaviour have been proposed.…”
Section: Introductionmentioning
confidence: 99%